2014
DOI: 10.1038/jcbfm.2014.86
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic Fractional Anisotropy Predicts Accrual of Cerebral White Matter Damage in Older Subjects with Small-Vessel Disease

Abstract: White matter hyperintensities (WMHs) and lacunes are magnetic resonance imaging hallmarks of cerebral small-vessel disease, which increase the risk of stroke, cognitive, and mobility impairment. Although most studies of cerebral small-vessel disease have focused on white matter abnormalities, the gray matter (GM) is also affected, as evidenced by frequently observed lacunes in subcortical GM. Diffusion tensor imaging (DTI) is sensitive to subtle neurodegenerative changes in deep GM structures. We explored the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…In addition, it is of interest that increased FA in the thalamus was not accompanied by a significant change in MD. One explanation for our finding is that, although reduced rather than increased FA is considered the hallmark DTI correlate of microstructural WM damage, a more restricted intracellular (intraaxonal) water compartment associated with cytotoxic edema could result in increased FA with relatively low MD or no MD change, which supports the possibility that the observed DTI changes in the thalamus might primarily reflect WM injury [Cavallari et al, 2014]. A more plausible explanation is that extraaxonal degeneration in the thalamic nuclei might lead to increased FA with little or no MD change [Hannoun et al, 2012].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In addition, it is of interest that increased FA in the thalamus was not accompanied by a significant change in MD. One explanation for our finding is that, although reduced rather than increased FA is considered the hallmark DTI correlate of microstructural WM damage, a more restricted intracellular (intraaxonal) water compartment associated with cytotoxic edema could result in increased FA with relatively low MD or no MD change, which supports the possibility that the observed DTI changes in the thalamus might primarily reflect WM injury [Cavallari et al, 2014]. A more plausible explanation is that extraaxonal degeneration in the thalamic nuclei might lead to increased FA with little or no MD change [Hannoun et al, 2012].…”
Section: Discussionsupporting
confidence: 67%
“…A more plausible explanation is that extraaxonal degeneration in the thalamic nuclei might lead to increased FA with little or no MD change [Hannoun et al, ]. This notion suggests that increased FA in the thalamus may reflect microstructural damage within the thalamic GM nuclei rather than WM damage, as supported by our finding of thalamic GM atrophy [Cavallari et al, ]. Nevertheless, the biophysical basis of pathologically increased FA remains to be elucidated in human.…”
Section: Discussionmentioning
confidence: 66%
“…Studies on LA were entirely crosssectional [47,57,62] whereas studies related to VCI were predominantly longitudinal. Longitudinal studies [63,67,70,[78][79][80][81][83][84][85][86] focused on characterizing the disease progression using DTI measures.…”
Section: Diffusion Tensor Imaging (Dti)mentioning
confidence: 99%
“…Important in this context, the prognostic value of baseline local DTI parameters for WML progression within a 4-year period has been reported. 72 So far, there have been only a few studies assessing the association between microstructural tissue alterations and cerebral vascular changes. A recent longitudinal study showed an association between small asymptomatic diffusion-weighted imaging hyperintense lesions and microstructural alterations and linked these results to vascular cognitive impairment.…”
Section: Microstructural Changes In Normal-appearing Brain Tissuementioning
confidence: 99%